Perkembangan 20 Tahun Penelitian Manajemen Laba - Perwitasari, Dian; Kirana Wandira, Raras; Nurrahmawati, An (Akuntansi: Jurnal Akuntansi Integratif, 2020)
This study assessed the development of research publications on earnings management. The main aim of this study is to orient researches in creating a theoretical framework and to guide researchers who are new in earnings management research so that they know which journals and authors can be used as references when studying this phenomenon. This study uses several bibliometric indicators. All research publications related to the earnings management in the Scopus database are analysed. The authorship, number of citations, year of publication, source of articles and the publisher, institutions and countries, document types and categories, language, and author keywords are identified. The results of these analyses showed that research on earnings management is still considered an interesting and relevant issue to be studied.